AB0347 The Retention Rates of The Second Biologic Agents in Rheumatoid Arthritis Patients with Inadequate Response To TNFα Inhibitors, Single-Center, Retrospective, Observational Study. (15th July 2016) - Kikuchi, E.; Uekubo, K.; Aoki, N.; Yoshioka, T.; Okai, T.
Abstract : Background: There are few data about the safety of biologics switching for rheumatoid arthritis in clinical practice conditions. Objectives: To analyze the retention rates of biologics switch therapies for rheumatoid arthritis patients after inadequate response to TNFα inhibitors. Methods: Data was collected retrospectively from medical records of RA patients in our center. We divided the RA patients with inadequate response to TNFα inhibitors into the two groups. The first group is consists of the patients who switched to other TNFα inhibitors. The other is consists of the patients who switched to non-TNFα inhibitors. We analyzed the retention rate of each group by Kaplan-Meier curves and log-rank test. Results: In the " another TNFα inhibitor " group (31 cases, 59.4±14.8 years, women: 90.3%, ACPA-positive 74.2%, MTX use 93.3%, oral steroid use 30.0%), infliximab (IFX): 11, etanercept (ETN): 7, adalimumab (ADA): 9, golimumab (GLM): 2 and certolizumab pegol (CZP): 2 are administered as the first biologics, discontinued due to adverse events: 4, inadequate efficacy:26 and other: 1 respectively), IFX: 4, ETN: 17, ADA: 3, GLM: 2 and CZP: 5 were chosen as the second biologics. The cumulative retention rates of the second biologics in 12 and 24 months were 0.628 and 0.547 respectively. The reasons for discontinuation of secondary used TNFα inhibitors were adverse events: 4 and inadequate efficacy: 9. In the " non-TNFα inhibitor " group (27 cases, 64.0±14.2 years, women: 83.3%, ACPA-positive 92.6%, MTX use 57.7%, oral steroid use 30.8%, IFX: 8, ETN: 13, ADA: 4, GLM: 1 and CZP: 1 are administered as the first biologics, discontinued due to adverse events: 7, inadequate efficacy: 20 respectively), tocilizumab (TCZ): 8 and abatacept (ABT): 19 were chosen as the second biologics. The cumulative retention rates of the second biologics in 12 and 24 months were 0.920 and 0.871 respectively. Three TCZ used patients were discontinued biologics within 24 months due to adverse events: 2 and inadequate efficacy: 1. There was a significant difference in the retention rates in the two groups (log-rank test, p=0.0095) (figure ). In the "non-TNFα inhibitor" group, the cumulative retention rates of TCZ and ABT in 24 months are 0.822 and 1.000 respectively. There is no significant difference (log-rank test, p=0.277). Conclusions: Our data suggested that non-TNFα inhibitors can be used for a long period for the RA patients with inadequate response to TNFα inhibitors. References: Hirabara S, et al. Clin Rheumatol. 2014, 33: 1247–54 Deighton C. Nat Rev Rheumatol. 2009, 5:596–7 Disclosure of Interest: None declared